Early Involvement by Extra-Pulmonary Sarcoidosis Presenting with Epigastric Pain (Global Journal of Medical Research, 2018)
Gastrointestinal sarcoidosis leads to the formation of non-caseating granulomas in any GI-related organ. Overt presentation is rare, with subclinical involvement of the GI tract estimated to be higher. The diagnosis of GI sarcoidosis depends on clinical manifestations of the disease, and when possible, histology demonstrating characteristic non-caseating granumolas. Diseases capable of producing a similar clinical and/or histological picture must be excluded. Herein, we report a case of a patient with pulmonary sarcoidosis in remission, presenting with mild epigastric pain, and subsequently diagnosed with biopsy-proven gastric sarcoidosis..
Keywords: sarcoidosis; GI sarcoidosis; extra-pulmonary sarcoidosis; gastrointestinal diseases